Role in the Forest Village Community-Based Forest Management Sustainable Development - Sandy Kurnia Christmas; Marzellina Hardiyanti; Syailendra Anantya Prawira (Journal of Judicial Review, 2021)
The Village Forest Society Institution is present on the basis of the existence of a Joint Community Forest Management (CBFM) program from one form of Corporate Social Responsibility (CSR). This PHBM policy seeks to empower communities around forest areas with managed areas under the authority of Perum Perhutani in the Provinces of Central Java, East Java, West Java and Banten, except for conservation forests which are implemented to provide welfare efforts for forest village communities so that they can participate in enjoying the results. forest production through a sharing system based on SK. Directors of Perum Perhutani No.682 / KPTS / DIR / 2009 concerning Guidelines for Collaborative Forest Resource Management, Law on Forestry, Village Law, and other supporting legislation..The role of LMDH is needed so that the partnership system in PHBM is able to reach forest village communities through an institution that is formed as an institution that receives delegations from the central / regional government in the management of production forests in the area specified in PP No. 72 of 2010 concerning State Forestry Public Company. With the existence of this LMDH, it is ecpected to be able to provide welfare for the communites around the forest and jointly manage forests based on sustainable development, so that the sustainability and availability of forest resources for future generations can be maintained.